The Analysis of The Impact of Responsibility Accounting on Production Cost Control - Wirananda, Henny Andriyani; Harahap, Wilda Sri Munawaroh (Lembaga Riset Ilmiah, 2024)
This study was written to determine the effect of responsibility accounting on controlling production costs at PT. Medan Grand Mopoli. The research method used in this research is descriptive qualitative. As for the subject of this research was conducted at PT. Mopoli. The object of this research is the production cost report of PT. Grand Mopoli. Data collection techniques in this study were using observation techniques, documentation techniques and interview techniques. In this case the research uses descriptive analysis techniques. The results of the study show that responsible accounting has not been implemented properly because it is seen from the cost of technology and every year it experiences losses (unfavorable) or the realization is higher than the budget